Benefits from the remote monitoring of railway assets. Issue 2 (2nd June 2017) - Armstrong, John; Preston, John
Abstract : Railway infrastructure already has some 'smart' characteristics, in that it 'knows' where trains are located and can sometimes detect track and other equipment faults. There is considerable scope to increase these capabilities. There is also a significant and urgent need for such improvements: railways have limited operational flexibility and face increasing passenger and freight traffic demand on existing infrastructure. The reliable provision of additional capacity requires improved system 'self-knowledge' for traffic control and management purposes, as well as for system reliability and safety. The use of smart infrastructure for fault prediction and the guidance of preventive maintenance helps to maintain operational capacity. This approach also helps to reduce track access requirements for traditional maintenance and renewals activities, thus increasing network availability and total capacity. Climate change presents the railway industry with significant challenges, notably in terms of flooding and earthworks failures resulting from increased rainfall intensity. Smart infrastructure includes the prediction and monitoring of such events to maintain safety and enable the timely implementation of operational contingency plans. This paper draws upon a range of sources to identify the needs for and potential benefits of increased deployment of smart infrastructure and other assets on railways in Britain and elsewhere.